Philosophische Theologie im Umbruch (II/1) Wider den ungöttlichen Gott - Infragestellung Philosophischer Theologie durch Fideismus und Atheismus - Wucherer-Huldenfeld, Augustinus Karl (2014)
For Philosophical Theology in Transition is the Challenge of Fideism and Atheism very important, because they are both against a Ungodly God.